Multibody dynamic analysis of a heavy load suspended by a floating crane with constraint-based wire rope. (15th November 2015) - Ham, Seung-Ho; Roh, Myung-Il; Lee, Hyewon; Ha, Sol
Abstract: In this study, we derived a Discrete Euler–Lagrange (DEL) equation to represent the motion of a multibody system, in which many bodies are connected physically by joints or wire ropes. By discretizing and re-formulating the traditional Euler–Lagrange equation, we obtained a discrete time integrator, called the Stömer–Verlet method. Similarly, we discretized the equations of constraints of joints and wire ropes by the midpoint rule. Then, we adapted regularization and stabilization methods, to overcome numerical instability and the stiffness problem. The DEL equation can be formulated automatically, by defining the equations of joint constraints and their derivatives. In addition, the stretching of the wire rope is mathematically modeled as constraints for stability. To apply the DEL equation to a floating vessel, hydrostatic and hydrodynamic forces are considered as external forces. We applied the DEL equation to a mass–spring system with the large spring coefficient. And we tested a spring pendulum modeled by a constraint-based wire rope. Despite the large spring coefficient, the DEL equation with the constraint-based wire rope shows relatively stable motion. We tested the automatic formulation by three-dimensional multiple pendulums. Finally, we simulated a floating crane and a heavy load connected by constraint-based wire rope, based on set of regular waves with different wave heights, directions and periods. Highlights: The regularized Discrete Euler-Lagrange (DEL) equation with constraints is derived. The stretching of a wire rope is mathematically modeled as constraints. We apply the DEL equation to several test cases to compare the stability and performance. We simulate a floating crane operating a heavy load connected by a constraint-based wire rope based on set of regular waves.